4D-tracking in the 10-ps range: A technological perspective - Lai, Adriano (Frontiers in Physics, 2022)
The present paper focuses on recent and ready-to-come advancements concerning high-resolution 4D-tracking with a perspective approach. Four-dimensional-tracking techniques (particle tracking with timing information for each detection point) have revealed a necessity for the next and next-to-next generations of high-energy physics experiments to cope with the increasing luminosity and consequent event pile-up in the beam collision region. Such a decisive challenge concerns both detection and processing technologies at an unprecedented level of difficulty. In addition to the high performance required in space–time measurement precision (some tens of picoseconds resolution in timing and about 10 µm resolution in space), an extremely high radiation hardness is demanded for such technologies together with an extremely high read-out and processing capability. Emerging experimental solutions for sensors and electronics against such challenges are presented here.